Folic Acid Rescues Valproic Acid-Induced Morphogenesis Inhibition in Neural Rosettes Derived From Human Pluripotent Stem Cells - Zhang, Xiao-zuo; Huo, Hai-qin; Zhu, Yu-qing; Feng, Hao-yang; Jiao, Jiao; Tan, Jian-xin; Wang, Yan; Hu, Ping; Xu, Zheng-feng (Frontiers in Cellular Neuroscience, 2022)
The ability of human pluripotent stem cells to specialize in neuroepithelial tissue makes them ideal candidates for use in the disease models of neural tube defects. In this study, we cultured human pluripotent stem cells in suspension with modified neural induction method, and immunofluorescence staining was applied to detect important markers associated with cell fate and morphogenesis to verify the establishment of the neural tube model in vitro. We carried out the drug experiments to further investigate the toxicity of valproic acid (VPA) exposure and the potential protective effect of folic acid (FA). The results demonstrated that neural rosette undergoes cell fate speciation and lumen formation accompanied by a spatiotemporal shift in the expression patterns of cadherin, indicating the model was successfully established. The results showed that VPA caused morphogenesis inhibition of lumen formation by altering cytoskeletal function and cell polarization, which could be rescued by FA supplement.